Port City Architecture: Reading Paintings as an Architectural Design Method - TANIŞ, Fatma (TU Delft OPEN, 2021)
This article addresses the role and the importance of the 19th-century narratives and depictions of port cities in contemporary architectural design with a specific focus on paintings. In the last decades, cities the world undertook a large number of urban regeneration projects along waterfronts. In this way, vacant sites on waterfront areas became an opportunity to apply contemporary architectural design; however, many of those projects resulted in generic buildings failing to establish relationships with their landscape, environs, and the history of port cities. High-rise buildings, for instance, began to dominate waterfronts in many of the port cities (e.g., in London, Liverpool, Rotterdam, Baltimore). The land was simply used as a “site” by developers, and the contemporary architectural design failed to address the specificity of the architecture and caved in to the demands which had little to do with the possibilities of place. This article showcases a library and concert hall project realised in Bodø, Norway, to provide insight into an alternative model, where the architecture is situated specifically in response to the port condition and acts as a mediator between port, city and landscape. An interview with the architect Daniel Rosbottom, founder of the architecture firm DRDH which designed the project, provided insight into the design process. As Rosbottom elaborated broadly, a 19th-century painting of church San Giorgio Maggiore in Venice h, by the English painter J.M.W Turner was used as an inspiration for the design process. The embedded knowledge in the painting informed the project at various levels and turned a site into a place on the waterfront of Bodø. The design process analysis reveals similarities and significance of paired relations between artworks and architectural design and hints that the remedy of the contemporary architectures in port cities may lie in port cities’ own (immaterial) resources.